New records of the rare Histiotus magellanicus (Chiroptera, Vespertilionidae) and other bats from central Patagonia, Argentina - Giménez, Analía Laura (2012)
Histiotus magellanicus (Philippi, 1866) is a poorly known Patagonian bat. Here we report on nine newly captured specimens and one unpublished locality from museum specimen that significantly improve our knowledge of this species' distribution, by incorporating two Argentine provinces and reducing the distributional gap between northern and southern historical records. The new records confirm H. magellanicus as a Subantarctic Forests endemic. In addition, we report new specimens and localities from four poorly known Patagonian bats for Chubut province: Histiotus macrotus, Myotis chiloensis, Lasiurus varius (Vespertilionidae) and Tadarida brasiliensis (Molossidae).